Genetic diversity of mitochondrial D‐LOOP sequences in the spotted scat (Scatophagus argus) from different geographical populations along the northern coast of the South China Sea. (16th November 2020) - Peng, Min; Zhu, Weilin; Yang, Chunling; Yao, Jiuxiang; Chen, Huifang; Jiang, Weiming; He, Zhenhan; Li, Qiangyong; Liu, Qingyun; Zhao, Yongzhen; Lin, Yong; Chen, Xiaohan; et al.
Summary: The genetic diversity of 289 spotted scat ( Scatophagus argus ) from seven populations along the northern coast of the South China Sea was studied by analyzing the full‐length sequences of the mitochondrial control region (D‐LOOP). The S. argus D‐LOOP sequence was 1, 004–1, 010 bp long and contained 156 variant sites. The seven studied S. argus populations had a high degree of genetic diversity (haplotype diversity [Hd] = 0.99135; nucleotide diversity ( π ) = 0.01313). There was no obvious genetic differentiation among the seven geographical populations and gene exchange was frequent (Fst = −0.01867–0.01117, p  > .05). Four distinct mitochondrial lineages were identified in the phylogenetic tree and the haplotype network. The between‐lineage Fst was 0.71690–0.84940 ( p  < .001), but these lineages showed no obvious phylogeographic pattern. Based on D‐LOOP mutation rates, we estimated that the four lineages diverged approximately 513, 800–93, 600 years ago, during the Eocene ice age, at which time falling sea levels may have led to population segregation. We estimated that S. argus population expansion occurred approximately 2.29–0.68 million years ago, during the late Pleistocene. During this period, sea levels rose again, allowing previously separated lineages to come into sympatry, which eventually gave rise to a highly genetically diverse population without pyhlogeographic structure. Here, we characterized the genetic structure and differentiation of seven S. argus populations from the northern coast of the South China Sea. Our results suggested that the seven S. argus populations from the northern coast of the South China Sea have a relatively low level of genetic variation and can be considered a single unit for the purposes of fishery development, utilization, and management.